Does Learning Matter for Wages in Korea? International Comparison of Wage Returns to Adult Education and Training - Yoonsoo Park (KDI Journal of Economic Policy, 2022)
This study compares the wage equation in Korea to those in other countries, focusing on the wage returns to adult education and training (AET) participation. It is found that the wage compensation structure in Korea is associated mainly with job characteristics such as tenure and workplace size rather than with worker characteristics such as AET participation and cognitive abilities. It is also found that Korea's AET participation is skewed toward non-job-related AET, relative to the situations in other countries. These findings imply that the link between a worker's productivity and wage shou ld be strengthened in order to incentivize workers to invest in AET relevant to the labor market.
Keywords: J24; J31; P46; 330; Adult Education and Training; Lifelong Learning; Wage Education; Skills